TECHNOLOGY AND TEACHER PROFESSIONALISM: ADAPTING HYBRID AND DIGITAL LEARNING - Abdul Halim (Jurnal Konseling Pendidikan Islam, 2025)
The digitalization era has fundamentally transformed educational landscapes, demanding transformation in teacher professionalism regarding technology integration in learning. The COVID-19 pandemic accelerated the adoption of hybrid and digital learning, creating new challenges in teachers' pedagogical competencies. Teacher professionalism is now measured not only by conventional teaching abilities but also by proficiency in utilizing technology as effective learning media. This research aims to analyze technology adaptation in teacher professionalism, identify hybrid learning challenges, and formulate strategies for developing teachers' digital competencies. The study employs library research methodology with qualitative descriptive analysis of various current academic literature sources. Data collection was conducted through systematic review of national and international journals from 2019-2024. Data analysis utilized content analysis techniques with source triangulation to ensure findings validity. Results indicate that technology adaptation requires comprehensive transformation in teachers' pedagogical, personality, social, and professional competencies. Hybrid learning provides flexibility but demands more complex time management and technological skills. Teacher professionalism development strategies must include continuous training, technical mentoring, and adequate technological infrastructure development.